Mapping out market drivers of improved variety seed use: the case of sorghum in Tanzania - Kalema, Elizabeth Phineas; Akpo, Essegbemon; Muricho, Geoffrey; Ringo, Justin; Ojiewo, Christopher Ochieng; Varshney, Rajeev K. (Elsevier, 2022)
It is understood that the grain market pulls the seed market. The problem of low quality prompted failure of traders and processors to purchase most of the farmers' grain to subsequently drive the use of improved variety seed. The aim of this study is to identify drivers that persuade farmers to use improved variety seeds for grain production. It also assesses factors affecting market participation among small-scale farmers. Descriptive analysis, Binary Logistic model, Probit model and gross margin analysis was conducted from random selected sample of 212 individual farmers, 63 grain off-takers, 3 extension officers and 7 seeds producers through structured interviews. In additional, 80 farmers were interviewed through 10 focus group discussion. The results showed that taste, preferences and price difference between grain and seed were significant and positive drivers that influenced the decision of farmers to use improved varieties at 47% and 0.007%, respectively. Factors such as group membership and farm size were significantly positive affecting farmer's market participation while age was negatively significant affecting farmer's market participation. Gross margin was computed to compare the profit margin between users and non-users of improved variety seeds, where users had high profit margin (530 979.89Tsh/Ha) compared to non-users (472 885.94Tsh/Ha), because non-users incurred high seed cost (54 504.84Tsh/15kg) compared to users of improved variety seeds (39 329.94Tsh/kg). Also, users obtained high grain revenue compared to non-user at 1 353 268.37Tsh and 848 249.11Tsh, respectively. Efforts should be made by value chain actors and other agricultural actors to support farmers based on market demand so they could benefit from high grain quality, quantity and promising grain market.